2011
DOI: 10.2147/ijn.s22335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phospholipid composition on cationic emulsions/DNA complexes: physicochemical properties, cytotoxicity, and transfection on Hep G2 cells

Abstract: Background Cationic nanoemulsions have been recently considered as potential delivery systems for nucleic acids. This study reports the influence of phospholipids on the properties of cationic nanoemulsions/DNA plasmid complexes. Methods Nanoemulsions composed of medium-chain triglycerides, stearylamine, egg lecithin or isolated phospholipids, ie, DSPC, DOPC, DSPE, or DOPE, glycerol, and water were prepared by spontaneous emulsification. Gene transfer to Hep G2 cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
4
3
0
Order By: Relevance
“…This was evident in the differences in the cellular toxicities of the two nanocapsules at the highest tested concentration (1 mg/mL). This finding correlates to the presence of the cationic surfactant CTAB in high concentration, which is in agreement with previous reports 39 . In addition, the marked difference in viability between the HA-based nanocapsules and the surfactant solution composed of Tween®80/Solutol/CTAB at 350 μg/mL suggests the beneficial effect of HA surrounding the surfactant layer as well as the correct isolation of the system from the free surfactants 40 .…”
Section: Discussionsupporting
confidence: 93%
“…This was evident in the differences in the cellular toxicities of the two nanocapsules at the highest tested concentration (1 mg/mL). This finding correlates to the presence of the cationic surfactant CTAB in high concentration, which is in agreement with previous reports 39 . In addition, the marked difference in viability between the HA-based nanocapsules and the surfactant solution composed of Tween®80/Solutol/CTAB at 350 μg/mL suggests the beneficial effect of HA surrounding the surfactant layer as well as the correct isolation of the system from the free surfactants 40 .…”
Section: Discussionsupporting
confidence: 93%
“…The main physicochemical characteristics of NE and complexes obtained in this study were in accordance with those reported in previous studies using NE obtained through microfluidization under similar conditions [40,47]. The correlation between the increase in charge ratio and the efficiency of oligonucleotide complexation corroborates data already reported in the literature [48][49][50][51]. In addition, an efficient system for CD73 siRNA in vitro and in vivo delivery was developed.…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Figure 3, HDAS-PEG as well as liposomes containing HDAS-PEG did not show any effect on the viability of these two cell lines. In general, cationic lipids and phospholipids with low phase transition temperature are toxic to cells (Fraga et al, 2011; Senior et al, 1991). Liposomes bearing rigid lipid chains provide more stable and less toxic interface between biological system and the formulation.…”
Section: Resultsmentioning
confidence: 99%